P283 Effects of odours on electrophysiological responses to laser pain stimuli. Issue 9 (September 2017) - Fallon, Nicholas; Cook, Stephanie; De Soto, Vicente; Kokmotou, Katerina; Stancak, Andrej
Abstract : Background: Previous studies have shown increases in subjective experience and electrophysiological processing of experimental pain during induction of negative emotions with concurrent multi-modal sensory stimuli. The goal of the present study was to analyse spatio-temporal activation patterns underlying processing of acute pain during exposures to affectively valenced odour stimuli. Methods: Negative, positive, and neutral (clean air) odour pulses were presented to 17 healthy participants via an olfactometer whilst brief noxious laser stimuli were administered to the dorsum of the left hand. Brain activity was monitored using electroencephalography (EEG) and participants rated the quality and intensity of pain and odour stimuli following each trial using visual analogue scales. Subjective ratings of pain stimuli and laser evoked potentials (LEPs) were analysed to evaluate the influence of valenced odours on subjective and electrophysioloigical aspects of pain processing. Results: Analysis of pain ratings revealed no difference in pain intensity, or specific pain qualities across the different odour conditions. Individual LEP components demonstrated expected correlations with specific aspects of pain perception, but did not differ between odour conditions. Conclusions: Contrary to research from other sensory modalities, the findings of the present study suggest that affectively valenced odours do not overtly influence aspects of subjective pain perception or electrophysiological processing of acute pain. This may be due to the influence of top-down factors affecting split perception between competing sensory stimuli, which may interact differently for pain and olfactory perception compared to other modalities.